2016
DOI: 10.1021/acs.cgd.6b01462
|View full text |Cite
|
Sign up to set email alerts
|

Iso-Structurality Induced Solid Phase Transformations: A Case Study with Lenalidomide

Abstract: Lenalidomide (LDM) is a thalidomide analogue known for its immunomodulation, antiangiogenic, and antineoplastic properties. However, to date, only two forms of lenalidomide [Form-1 (anhydrous) and Form-2 (hemihydrate)] are reported in the literature. Through a comprehensive polymorph screening herein, we report five forms of lenalidomide [Form-3 (DMF-solvate), Form-4 (anhydrous), Form-5 (DMSO solvate), Form-6 (acetone solvate), and Form-7 (dihydrate)]. Single crystal structures (for all forms) are established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 71 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Analyses of crystal structures for MFA reveal the existence of identical or very similar crystal structures for each TFA type. Such a high degree of matching suggests that, by exploring the landscape for a model system, one can practically find possible crystal structures for other similar systems (Chennuru et al, 2017). Similarly, crystal structures of single-component TFA and MFA are analysed.…”
Section: Isostructurality and The Relationship With Crystal Structuramentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of crystal structures for MFA reveal the existence of identical or very similar crystal structures for each TFA type. Such a high degree of matching suggests that, by exploring the landscape for a model system, one can practically find possible crystal structures for other similar systems (Chennuru et al, 2017). Similarly, crystal structures of single-component TFA and MFA are analysed.…”
Section: Isostructurality and The Relationship With Crystal Structuramentioning
confidence: 99%
“…On the other hand, isostructurality has advantages such as reliable structure versus property knowledge transfer (Chennuru et al, 2017;Wood et al, 2012;Reddy et al, 2006;Krishna et al, 2016;Saha & Desiraju, 2017b), and formation of solid solutions for tuning physicochemical properties (Elgavi et al, 1973;Vangala et al, 2002;Pigge et al, 2006). In general, polymorphism and isostructurality are perceived as opposite phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining three structures exist with more complex forms of hydrogen bonding. Compound 195 [171] (Figure 58) is a second form of 191 whose structure is quite different. The primary interaction is between the imide NH and the lactam carbonyl, leading to a C(7) ribbon structure as shown.…”
Section: Glutarimidementioning
confidence: 99%
“…All solvates but water belong to the same group as two trospium chloride polymorphs [113]. Dehydration and desolvation of lenalidomide follow "isostructurality" in crystal packing: All solvates at heating convert to its' thermodynamically stable anhydrous form, whereas all hydrates upon dehydration convert to a metastable anhydrous polymorph able to transform upon further heating to the stable polymorph [114]. Analysis of H-bonding and crystal packing similarity for the crystal structures of vitamin D analogs showed that various conformations of its A-ring are predetermined by H-bonding of hydroxyl group both in crystals and in the binding pocket of the vitamin D receptor and that the exocyclic methylene group also influences H-bonding pattern in solids [66].…”
Section: Crystal Packing Similarity Toolmentioning
confidence: 99%